2012
DOI: 10.1007/s11418-012-0695-2
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal parasitic plants on diverse hosts with their usages and barcodes

Abstract: Medicinal properties of parasitic plants were investigated by means of ethnobotanical study in some areas of northeastern Thailand. Important traditional usages are: Scurrula atropurpurea nourishes blood, Dendrophthoe pentandra decreases high blood pressure, and Helixanthera parasitica treats liver disease. Their systematics were also determined. The research is based on findings obtained from 100 parasite-host pairs. Of these, eight parasitic species were recorded; they are members of two families, viz. famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
1
12
1
Order By: Relevance
“…On the other hand, interspecific variations of rbcL region were 0.064 and 0.042 for Loranthaceae and Santalaceae, respectively. Value of interspecific distances of rbcL region for Loranthaceae and Santalaceae reported in this study were similar to the results reported by Kwanda et al (2013), which was 0.032 -0.067.…”
Section: Barcoding Gapsupporting
confidence: 91%
See 2 more Smart Citations
“…On the other hand, interspecific variations of rbcL region were 0.064 and 0.042 for Loranthaceae and Santalaceae, respectively. Value of interspecific distances of rbcL region for Loranthaceae and Santalaceae reported in this study were similar to the results reported by Kwanda et al (2013), which was 0.032 -0.067.…”
Section: Barcoding Gapsupporting
confidence: 91%
“…In this study, an average sequence length of rbcL region was 738 -740 bp. This value was higher than the length reported by Kwanda et al (2013) who used the same rbcL region, but different primer base pairs (5'-ATGTCACCACAAACAGAGACTAAAGC-3' and 5'-GTAAAATCAAGTCCACCRCG-3'), showing 550 bp for Loranthaceae family (D. pentandra, D. lanosa, Scurrula atropurpurea, M. cochinchinensis, M. bradisianus, Helixanthera parasitica) and Santalaceae family (V. articulatum and V. ovalifolium).…”
Section: Dna Analysis and Nucleotide Base Compositioncontrasting
confidence: 56%
See 1 more Smart Citation
“…philippinensis (2) D. pulchella (1) (Kwanda et al 2013). Additionally, the matK gene marker has been identified in some medicinal Piper species .…”
Section: Resultsmentioning
confidence: 99%
“…DNA barcoding is the most reliable and applicable method for overcoming this problem (Hebert et al 2003, CBOL Plant Working Group 2009, Hollingsworth et al 2011. Several research groups suggested appropriate DNA barcoding regions in some plant groups, such as the matK gene (Siripiyasing et al 2012, the rbcL gene , Kwanda et al 2013, and the psbA-trnH spacer region . Standard barcodes used for most plant groups are matK gene, rbcL gene, psbA-trnH spacer, and ITS region identified by the CBOL Plant Working Group (2009), Chaveerach et al (2011), Hollingsworth et al (2011 and Monkheang et al (2011).…”
Section: Introductionmentioning
confidence: 99%